PENERAPAN TEKNIK PEMBELAJARAN THINK, PAIRE, SHARE, (TPS) DALAM MENINGKATAKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS VIII MTS SABILUL HUDA CANGKRING KARANGANYAR DEMAK - Ersila Devy Rinjani; Anas Rohman (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2018)
Teachers have an enormous share to foster motivation learners such as learning using ThingPaire Share (TPS). Enjoyable learning techniques, will make learners more enthusiastic infollowing the learning process, so that students are able to think in pairs and share ideas orideas. Such a comfortable atmosphere and learning techniques are expected to transformlazy, unenthusiastic, indifferent learners and do not show positive activities in the learningprocess to be encouraged and grow the motivation of high learning spirit and optimalespecially in Indonesian language lesson. The purpose of national education should beeducation to strive towards the implementation of optimal learning. Good teaching andlearning process is characterized by the spirit that grows from learners, both from within andfrom outside so that the learner activities in the classroom well developed. Motivation tolearn becomes very important to have learners. Based on the above background, theresearcher in this study chose the title of Application of Think Paire Share LearningTechnique (TPS) in Improving the Motivation of Student Learning of Class VIII MTs SabilulHuda Cangkring. The results of experimental applying of learning with the technique of thinkpair share (TPS) to improve the motivation to learn the Indonesian language indicates that:(1) The teacher has a high enthusiasm to participate in implementing the learning by thinkingpair share (TPS) to improve student learning motivation, together with the researcher, (2)The application of learning by thinking pair share (TPS) technique to improve student'smotivation can be applied well in MTs Sabilul Huda Cangkring (3) students look enthusiasticand happy when applying of think pair share (TPS) increase learning motivation.Keyword: Think Paire Share Learning Technique, Motivation